Pengaruh Latihan Kognisi terhadap Pengambilan Keputusan Atlet Intelektual Rendah pada Cabang Olahraga Open Skill - Mohammad Hafiz Alfariz; Komarudin Komarudin; Mochamad Yamin Saputra; Geraldi Novian (Journal of Sport Coaching and Physical Education, 2024)
This research discusses the cognitive training model (life kinetic and brain gym) in relation to the decision-making of low-intellectual athletes in open-skill sports. Cognitive training is also often recommended in the training process and sport practice approaches to improve movement. The aim of this research is to determine the effect of cognitive training models (life kinetic and brain gym) on the decision-making of low-intellectual athletes in open-skill sports. The method used is an experimental method. The population used was athletes in open-skill sports, totaling 48 athletes. The sample of children taken was 27 athletes taken using a purposive sampling technique. This research instrument uses the Advanced Progressive Matrices (APM) Test and The Decision Style Questionnaire (DSQ) Test. The data analysis technique used was the paired sample t-test and the independent sample t-test, and the results of this study showed that there was a significant influence of the life kinetic and brain gym training models on the decision-making of low-intellectual athletes in open-air sports. skill, and there is no significant difference in influence between life kinetic and brain gym training on the decision-making of low-intellectual athletes in open-skill sports